Holy Infant Jesus Convent, Jalan Yahya Awal, 80100 Johor Bahru, Johor Darul Takzim - Chan, Min Wai; Loh, Dennis Ing Han; Lee, Ai Lyn; Ng, Siau Hue; Tan, Shandy Yen Hui; Sim, Tiong Wei (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Measured Drawing (Jabatan Senibina)) - Universiti Teknologi Malaysia, 2004